Pengaruh Kualitas Pelayanan Room Attendant terhadap Kepuasan Tamu Hotel Grand Sahid Jaya Jakarta - Sari, Windy Della (Jurnal Ilmiah Poli Bisnis, 2019)
This research is a quantitative descriptive study in accordance with the purpose of the study to describe the characteristics of a situation, namely identifying services provided by attendat rooms that can affect the satisfaction of the staying guests and the factors that need to be maintained. According to the research, it can be concluded that based on the results of the discussion on the analysis of the level of conformity there are several factors whose statements reach 100% even more, which means these factors can affect guest satisfaction because guests are satisfied with the services provided by room attendants, including a value of 101.4%, 102.9%, 102.8% and 103.3%. And also found that there is a degree of conformity between reality (x) and expectation (y) that is equal to 98.18%, which means that the quality of service provided by room attendants at Grand Sahid Jaya Hotel has given satisfaction to guests but can reach 100% or value maximum service must be improved so that guests feel more or more than their expectations.